Review of Graph Comprehension Research: Implications for Instruction - Shah, Priti; Hoeffner, James (Educational psychology review, 2002)
Graphs are commonly used in textbooks and educational software, and can help students understand science and social science data. However, students sometimes have difficulty comprehending information depicted in graphs. What makes a graph better or worse at communicating relevant quantitative information? How can students learn to interpret graphs more effectively? This article reviews the cognitive literature on how viewers comprehend graphs and the factors that influence viewers' interpretations. Three major factors are considered: the visual characteristics of a graph (e.g., format, animation, color, use of legend, size, etc.), a viewer's knowledge about graphs, and a viewer's knowledge and expectations about the content of the data in a graph. This article provides a set of guidelines for the presentation of graphs to students and considers the implications of graph comprehension research for the teaching of graphical literacy skills. Finally, this article discusses unresolved questions and directions for future research relevant to data presentation and the teaching of graphical literacy skills.